Different Theories Regarding the Origin of Caste System of Ancient India: Exploring the Development and Significance of the Ancient Indian Social System (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The ancient Indian society has developed twofold coordinated system of social organization. On the one side the whole human life is divided in to four stages namely Ashramas and on the other side the society is divided in to four strata namely varna. Both the systems are concerned with the organization and management of the individual as well as society. Together these two systems of varnas and Ashramas are known as Varnashrama Dharma, the ancient social system that was meant to assure spiritual and material prosperity for both society and the individual. Through this research paper the history of these two systems.